[A street in Trinidad] - (:unkn) unknown (My University, 2010)
The postcard shows wooden houses with galvanized roofs enclosed by wooden fences. In the background there is a small group of persons gathered around the electricity pole.
Colour:Sepia; Style: Landscape; Other: Bordered ,Divided
Keywords: Trinidad and Tobago; Postcards; Wooden-frame houses; Rural roads